Study of Pathological lesions and histochemistry of placenta in hypertension cases - Entissar Kanani (مجلة التربية والعلم, 2010)
ABSTRACT This study was conducted to investigate the histopathological and histochemical changes in hypertensive placentae as compared with normotensive placentae. The result showed presence of histopathologic lesions in hypertensive placentae represented by necrosis, fibrine deposition and desquamation of Cyncytiotrophobl asts as well as changes in maternal and fetal blood vessels. Also, the result showed histochemical changes represented by highly positive reaction with periodic acid schiffs (PAS) as compared with normotensive Placenta, and moderate positive with A.B at ph 2.5, and positive reaction with best carmine in hypertensive placentae. In concoulosion, this study showed presence of histopathological and histochemical changes in hypertensive placentae as compared with normotensive.